STUDY OF MICROSTRUCTURE, HARDNESS AND WEAR PROPERTIES OF SAND CAST Cu-4Ni-6Sn BRONZE ALLOY - S. ILANGOVAN (Journal of Engineering Science and Technology, 2015)
An alloy of Cu-4Ni-6Sn was cast in the sand moulds. The cast rods were homogenized, solution heat treated and aged for different periods of time. The specimens were prepared from the rods to study the microstructure, microhardness and wear properties. It was found that the aging process increases the hardness of the alloy significantly. It was due to the change in the microstructure of the alloy. Further, spinodal decomposition and the ordering reaction take place during the aging treatment. Specific wear rate was found to decrease with the hardness of the alloy. Coefficient of friction remains constant and is not affected by the aging process.